Comparison of gamma ray effects on EPROMs and E2PROMs - Vujisić Miloš; Stanković Koviljka; Vasić Aleksandra (Nuclear Technology and Radiation Protection, 2009)
This paper compares the reliability of standard commercial Erasable Programmable Read Only Memory (EPROM) and Electrically Erasable Programmable Read Only Memory (E2PROM) components exposed to gamma rays. The results obtained for CMOS-based EPROM (NM27C010) and E2PROM (NM93CS46) components provide the evidence that EPROMs have greater radiation hardness than E2PROMs. Moreover, the changes in EPROMs are reversible, and after erasure and reprogramming all EPROM components restore their functionality. On the other hand, changes in E2PROMs are irreversible. The obtained results are analyzed and interpreted on the basis of gamma ray interaction with the CMOS structure.